2016
DOI: 10.1111/hsc.12323
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of unmet needs for community social care services in England. A comparison of working carers and the people they care for

Abstract: Perceptions of unmet needs for community social care services in England. A comparison of working carers and the people they care for Article (Accepted version) (Refereed) Original citation: Brimblecombe, Nicola, Pickard, Linda, King, Derek and Knapp, Martin (2017) Perceptions of unmet needs for community social care services in England. A comparison of working carers and the people they care for. Health & Social Care in the Community, 25 (2). Abstract Previous UK research has found expressed unmet need for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…Earlier analysis of our sample at baseline found that there was a high level of perceived unmet need for services by both working carers and the people they cared for, particularly where unpaid care was provided for ten or more hours a week (Brimblecombe et al . ). Analysis of our longitudinal sample at follow‐on found that unmet need by working carers remained high two years later, but that many carers and the people they cared for experienced barriers to receipt of social care services and, as a result, carers were often forced to make accommodations to their working lives (Brimblecombe et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier analysis of our sample at baseline found that there was a high level of perceived unmet need for services by both working carers and the people they cared for, particularly where unpaid care was provided for ten or more hours a week (Brimblecombe et al . ). Analysis of our longitudinal sample at follow‐on found that unmet need by working carers remained high two years later, but that many carers and the people they cared for experienced barriers to receipt of social care services and, as a result, carers were often forced to make accommodations to their working lives (Brimblecombe et al .…”
Section: Discussionmentioning
confidence: 97%
“…Our questionnaires used validated questions from other surveys (for further details, see Brimblecombe et al . ). Additional questions were piloted with respondents who did not take part in the main study.…”
Section: Methodsmentioning
confidence: 97%
“…Finally, this study did not conduct dyadic interviews with informal caregivers. Studies involving the voices of caregivers’ point towards the existing differences in the various actor's perceptions (Brimblecombe, Pickard, King, & Knapp, ; Turcotte et al, ) and indicate that caregivers’ and care recipients’ rating of control over their daily life are mutually interdependent (Rand, Forder, & Malley, ). Another study explored dyadic associations of mastery beliefs among older partners and suggested that partners’ mastery beliefs matter for the health (behaviours) of older adults (Drewelies, Chopik, Hoppmann, Smith, & Gerstorf, ).…”
Section: Discussionmentioning
confidence: 99%
“…People receiving unpaid caring assistance may be reluctant to accept help from organised support services. The Survey of Carers in Households in England found that 15% of carers support people who would not want anyone else assisting them (Brimblecombe, Pickard, King, & Knapp, ). Furthermore, the barriers to employment reported by mental health carers may be related not just to the availability of formal assistance for their care recipients, but also the carer's assessment of the suitability, continuity and quality of these formal services.…”
Section: Resultsmentioning
confidence: 99%